2017
DOI: 10.1016/j.ghir.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Suckling induced insulin-like growth factor-1 (IGF-1) release in mother rats

Abstract: In conclusion, suckling induces IGF-1 release either by elevating PRL or GH. Long-loop feedback via IGF-1 in the GH axis can diminish this action.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
1
1
1
Order By: Relevance
“…It has been reported that suckling induced IGF1 release in rats during lactation [40]. However, a higher IGF1 overexpression in twin-bearing ewes as a consequence of double suckling was not observed during the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…It has been reported that suckling induced IGF1 release in rats during lactation [40]. However, a higher IGF1 overexpression in twin-bearing ewes as a consequence of double suckling was not observed during the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…The occurrence of turnover/lactogenesis has been reported during late lactation [41,42], as observed in the present study, where the mRNA of IGF1 (but not its receptor IGF1R) was overexpressed in single-bearing ewes at day 35 post-partum, which was explained by the suckling induced IGF1 release in rats during lactation [43]. However, we noticed that the group of twin-bearing ewes did not overexpress IGF1 in spite of double suckling (p > 0.05).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, insulinlike growth factor-1 (IGF-1) has also been suggested to play a role (Dobolyi and Leko, 2019). Prolonged intracerebroventricular IGF-1 was shown to stimulate dopamine secretion in the mediobasal hypothalamus and inhibit prolactin secretion from the pituitary (Leko et al, 2017a). In turn, a binding protein of IGF-1, IGF-binding protein-3 (IGFBP-3) is induced dramatically during lactation specifically in the arcuate nucleus (Leko et al, 2017b).…”
Section: Prolactin Released In the Postpartum Period In Response To Suckling In Mammalsmentioning
confidence: 99%